Liderazgo directivo en el desempeño docente del circuito Chantilín - Saquisilí 05d01 periodo lectivo 2016-2017. Manual de capacitación en liderazgo. - Chisaguano Taipe, Cinthia Paola (2017)
The research during the systematic and orderly process had the purpose of developing the Directing Leadership, for which after a given analysis was proposed as an objective to design a proposal of a manual of training which is going to boost the Directing Leadership with emphasis to the Circuito Chantilin - Saquisilí 05D01 circuit 2016-2017 school year, each Educational Unit is attended by three same authorities who are conformed by principal.Tch, Viceprincipal.Tch, Inspector.Tch it , has been determined within the specific objectives that were the following: to apply surveys between authorities Or the directive level in the educative institutions of the C01 circuit in order to determine the demands of training in the directive management with the purpose of optimizing the administrative management to; acquire the bibliographic sources required for the scientific and theoretical fundation of the research work; to desing manual of training about the directing leadership for optimizing the administrative and management processes. The following hypothesis was established for the development of the work: The directing leadership affects the teaching performance of the institutions of the Chantilin - Saquisilí Circuit, the following has been established as an independent variable: managerial leadership, and as a dependent variable teaching performance. The instruments that were used for this research were a survey in which the feasibility was determined in the development of a training manual for Leaders, in order to carry out the established proposal. The result of this research will be reflected in the team work that will be the source of development in the change of strategies and in the management of new leadership practices that is developed with innovative proposals for development that benefit the educational community, fulfilling With quality standards of quality the Ministry of Education requires